Combining Metabolomics and Transcriptomics to Reveal the Mechanism of Coloration in Purple and Cream Mutant of Sweet Potato (Ipomoea batatas L.) - Rong Zhang; Ming Li; Chaochen Tang; Bingzhi Jiang; Zhufang Yao; Xueying Mo; Zhangying Wang (Frontiers in Plant Science, 2022)
Purple sweet potato is considered as a healthy food because of its high anthocyanins. To understand the coloring mechanism and quality change between purple-fleshed sweet potato (cv. Xuzi201) and its cream fleshed mutant (M1001), a combined metabolomic and transcriptomic analysis was performed. The metabolome data showed that 4 anthocyanins, 19 flavones, 6 flavanones, and 4 flavonols dramatically decreased in M1001, while the contents of 3 isoflavones, 3 flavonols, 4 catechins, and 2 proanthocyanins increased. Transcriptomic analyses indicated that the expression of 49 structural genes in the flavonoid pathway and transcription factors (TFs) (e.g., bHLH2, R2R3-MYB, MYB1) inducting anthocyanin biosynthesis were downregulated, but the repressor MYB44 was upregulated. The IbMYB1-2 gene was detected as a mutation gene in M1001, which is responsible for anthocyanin accumulation in the storage roots. Thus, the deficiency of purple color in the mutant is due to the lack of anthocyanin accumulation which was regulated by IbMYB1. Moreover, the accumulation of starch and aromatic volatiles was significantly different between Xuzi201 and M1001. These results not only revealed the mechanism of color mutation but also uncovered certain health-promoting compounds in sweet potato.